Kewenangan Jaksa Dalam Melakukan Penggabungan Perkara Korupsi Dan Money Laundering (Studi Kejaksaan Tinggi Sumatera Utara) - Ismail Koto (Iuris Studia: Jurnal Kajian Hukum, 2021)
There are many facts that occur that the perpetrators of money laundering crimes commit money laundering crimes from the proceeds of their crimes and most are obtained from criminal acts of corruption. Money laundering actors carry out various modes to eliminate traces of their actions. Money Laundering (Money Laudring) as a crime has a characteristic that this crime is not a single crime but a double crime. The point is that the crime of Money Laundering is a form of crime committed by either a person or a corporation, although the prosecutor has the authority to combine corruption and money laundering cases, we rarely see the merger between these two crimes. This type of research is a normative juridical research. With the main problem in the form of How is the relationship between corruption as a Predicate Crime in Money Laundering? How is the prosecutor in carrying out his authority to combine Corruption Crimes and Money Laundering Crimes? What are the Prosecutor's Barriers in Merging Corruption Crimes and Money Laundering Crimes? In every anti-money laundering provision there must be an element called a predicate offence, which means that from the results of any crime that can be subject to the provisions of Article 3, Article 4 and Article 5 of Law No. 8 of 2010 concerning Crimes Money laundering. The crime of Corruption and Money Laundering has a very fundamental relationship or relationship. If there is a merger of investigations into cases of corruption and money laundering, the Prosecutor must make a description of the two crimes in one indictment so that the indictment is in the form of an alternative and the Prosecutor must prove the two crimes before the trial. Based on Article 141 of the Criminal Procedure Code (KUHP), it is stated that the Public Prosecutor can combine cases and make them into one indictment, if at the same time or almost simultaneously they receive several case files. The prosecutor's obstacle in merging Corruption Crimes and Money Laundering Crimes is that it requires a long investigation time, because investigators must always coordinate with PPATK (Financial Transaction Reports and Analysis Center) to track money and assets of the suspect and coordinate with related parties, in court against the trial process, namely the course of the trial process will take a long time